2023
DOI: 10.1002/jev2.12363
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of extracellular vesicle‐derived miR‐146a‐5p decreases progression of melanoma brain metastasis via Notch pathway dysregulation in astrocytes

Emma Rigg,
Jiwei Wang,
Zhiwei Xue
et al.

Abstract: Melanoma has the highest propensity of all cancers to metastasize to the brain with a large percentage of late‐stage patients developing metastases in the central nervous system (CNS). It is well known that metastasis establishment, cell survival, and progression are affected by tumour‐host cell interactions where changes in the host cellular compartments likely play an important role. In this context, miRNAs transferred by tumour derived extracellular vesicles (EVs) have previously been shown to create a favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“… 289 Similarly, miR-146a-5p is transferred to astrocytes via extracellular vesicles, down-regulating NUMB and activating the Notch pathway, thereby promoting melanoma brain metastasis. 290 Conversely, in the context of PTEN deficiency, Notch1 and Notch2 exhibit anti-tumor effects in BRAFV600E/PTEN-null-driven melanoma genesis. 291 Likewise, Rad et al reported that Notch4 acts as a tumor suppressor in melanoma.…”
Section: The Notch Signaling Pathway and Cancermentioning
confidence: 99%
“… 289 Similarly, miR-146a-5p is transferred to astrocytes via extracellular vesicles, down-regulating NUMB and activating the Notch pathway, thereby promoting melanoma brain metastasis. 290 Conversely, in the context of PTEN deficiency, Notch1 and Notch2 exhibit anti-tumor effects in BRAFV600E/PTEN-null-driven melanoma genesis. 291 Likewise, Rad et al reported that Notch4 acts as a tumor suppressor in melanoma.…”
Section: The Notch Signaling Pathway and Cancermentioning
confidence: 99%
“…miR-221 plasma levels are increased in melanoma patients, and are correlated with stage, recurrence, and disease progression [123]. Rigg E. et al demonstrated that miR-146a-5p is overexpressed in melanoma brain metastases and its knockdown results in a reduction of metastatic lesions [124]. On the contrary, other types of microRNA such as mirR-211, miR-542 3p, or miR-152-3p are downregulated in invasive melanomas [125].…”
Section: Micrornamentioning
confidence: 99%
“…miR-146a shows aberrant expression or function in neuroinflammatory diseases [109] and indirectly down-regulates pro-inflammatory factors (e.g., IL-1β, IL-6, and TNF-α [110]) as well as promotes oligodendrocyte precursor cells (OPCs) differentiation [111]. In addition, a study transferred miR-146a-5p to astrocyte via extracellular vesicles (EVs) and revealed its ability to inhibit the Notch signaling pathway [112]. It suggests that miR-146a may play a critical role in neurons and glial cells in the immature brain.…”
Section: Mirnasmentioning
confidence: 99%